Theoretical Views Underlying the Selection of Classroom Activities: Paying Attention to the Classroom of English Literature in EFL Context - Yazid Basthomi (TEFLIN, 2003)
This essay reviews literature on the theoretical views underlying the selection of activities for classrooms of English literature teaching in EFL context. The review include: 1) literary criticisms, 2) constructivism, and 3) research on students perceptions of classroom activities. One literary criticism, reader-response, is beheld to pose a similar spirit to that of the constructivist mode of teaching. Both reader-response and constructivist teaching perspectives require the teaching of English literature to focus on the students. This requires giving attention to the students ideology, horizon of expectation, and Ã¢â¬Åmalumat sabiqohÃ¢â¬Â (background knowledge) in order to situate the students to actively generate their own meanings, understanding, or knowledge of given literary works offered as class materials. Since the students personal ideology, horizon of expectation, and malumat sabiqoh are influenced or the socio-culture undergirding every student, the teaching of English literature needs to take into account such socio-cultural properties. Another point reviewed is the students perceptions of classroom activities. Consideration of combining the top-down mode of thinking, as offered by the reader-response and constructivism, and bottom-up mode of thinking, as offered by research on students perceptions of classroom activities, constitute the ending part of this essay.